If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a(a + -9)(a + -8) = 0 Reorder the terms: a(-9 + a)(a + -8) = 0 Reorder the terms: a(-9 + a)(-8 + a) = 0 Multiply (-9 + a) * (-8 + a) a(-9(-8 + a) + a(-8 + a)) = 0 a((-8 * -9 + a * -9) + a(-8 + a)) = 0 a((72 + -9a) + a(-8 + a)) = 0 a(72 + -9a + (-8 * a + a * a)) = 0 a(72 + -9a + (-8a + a2)) = 0 Combine like terms: -9a + -8a = -17a a(72 + -17a + a2) = 0 (72 * a + -17a * a + a2 * a) = 0 (72a + -17a2 + a3) = 0 Solving 72a + -17a2 + a3 = 0 Solving for variable 'a'. Factor out the Greatest Common Factor (GCF), 'a'. a(72 + -17a + a2) = 0 Factor a trinomial. a((8 + -1a)(9 + -1a)) = 0Subproblem 1
Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0Subproblem 2
Set the factor '(8 + -1a)' equal to zero and attempt to solve: Simplifying 8 + -1a = 0 Solving 8 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1a = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1a = 0 + -8 -1a = 0 + -8 Combine like terms: 0 + -8 = -8 -1a = -8 Divide each side by '-1'. a = 8 Simplifying a = 8Subproblem 3
Set the factor '(9 + -1a)' equal to zero and attempt to solve: Simplifying 9 + -1a = 0 Solving 9 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1a = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1a = 0 + -9 -1a = 0 + -9 Combine like terms: 0 + -9 = -9 -1a = -9 Divide each side by '-1'. a = 9 Simplifying a = 9Solution
a = {0, 8, 9}
| 6(2q-1)=2q+8q | | N+3.4=5.6 | | n/5+3-10=30 | | a(bx-2)=cx+6 | | 6(4.5y)-12=9 | | (a+9)(a+2)=0 | | p+0.06p=148.4 | | n*5+3-10=30 | | 5x-5=4x+7 | | 15-2x-2=10x+3x+2 | | 4-5x=2(7x-3) | | -8-5n=4m | | 2(-1)+5+3x-3=5x+9 | | 8=-5+x | | 2r+4=2r-5 | | 10D+40=10 | | 25=7+3k-17 | | 13-4x+2=3x-7x+2 | | 2p+3p= | | 1+(-40+5x)=2+-1(x+5) | | 8=-5+8 | | -4.4-1.21z= | | 5x-12+15x-7+9-2x=-15 | | 12-7x-10=x-8x+2 | | t^2-2=0 | | 3a+4(2a-17)=-13 | | 9.99x+.25=113.74 | | 32x-21+-5x+30= | | 1=6p+6-p | | -(3x+2)-(x-1)=(2x-2)-(2x+4) | | 10-3x-1=7+3x+2 | | 1+5(x-8)=2-1(x+5) |